Labor e reprodução social: as marcas da transição rural urbana na trajetória de trabalhadores rurais migrantes do setor da construção na paraíba - Menezes, Maria Clara Lima de (2023)
This research analyzes how the Construction Sector becomes attractive, both in objective terms – of work, salary, income, job opportunities etc. – and in symbolic terms, by perceiving the space that this activity occupies in the lives of rural migrant workers as the only – if not the only – possible job opportunity in the capital of Paraiba. Thus, it receives a labour force used to flexible and unstable work that tends to adjust more easily to its own dynamics, in the same motto of flexibility that structures the brazilian labour market. For the methodological approach, qualitative methods were adopted, from the realization of semi-structured interviews and indepth to compose the analysis of life-work trajectories and the field notebook. We also obtained help from quantitative tools which were in charge of better outlining the sector's objective conditions – employment, income, number of workers, schooling, formality and informality levels, among other aspects. This quantitative research was guided from the search in portals of secondary data – IBGE, RAIS, CAGED and CBIC – as well as the making of graphs, tables, charts and quantitative and illustrative maps arising from primary data collected during the field research. The union between the adopted methods served us to better analyze focal characteristics of our discussion, such as: the eternal conflict between rural and urban areas as spaces under construction and the work conditions present in the brazilian labour market, whether in a more urbanized or more ruralized environment. With these movements of migration/transition between one place and another, seen as the center of our discussions, we could perceive what are the past and present experiences and the future expectations of these workers; as well as, how this sector shelters this male workforce, with low formal education and that has in the city its main horizon of formalized work.